The Potential for a Networked Ionospheric Sounding Constellation - A. T. Chartier (Space Weather)
Abstract A novel networked sounding constellation mission concept is proposed. Radio sounding is the original sensing method that proved the existence of the ionosphere. Satellite‐borne sounders provided the first global observations of the terrestrial ionosphere and plasmasphere, as well as the Martian ionosphere. Networked sounding, where signals are transmitted and received across multiple instruments, has been used on the ground since the first days of ionospheric observation. This paper proposes networked sounding from space, to produce measurements of the F‐layer peak, enhanced E‐layers, regions of turbulent structuring, the topside scale height (or transition height) and potentially the plasmapause. The principal advantage of sounding over other methods is direct measurement of the peak density, where a networked implementation greatly increases spatial data coverage because it provides multiple unique signal paths through the ionosphere at different frequencies. Major advances in satellite software‐defined radio, deployable antennas, signal processing and data analysis have been made in recent years, such that a networked sounding constellation could be built at realistic cost—either as a hosted payload on commercial buses or on dedicated CubeSats.